Proposed Circular Bamboo House Miniature (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
A circular bamboo house can minimize the use of traditional house sources. A natural material had a high strength-to-weight ratio useful structures. This material can include design elements that take advantageof the hurricane. Many bamboo houses have a house structure with capable materials to defend any nature attack, such as typhoons, due to their circular shapes. This study used an experimental research design to explain and evaluate the research project. Purposive sampling was also utilized,with two professional groups of respondents, that is, civil engineers and architects, who answered the following questions. This is the floor plan of the study where a bamboo house was installed on San Carlos, Negros Occidental for housing. This type of housing also uses frequency and percentage to summarize values and organize data (Hardy, 2019). The weighted mean was used to determine the average weight values (Gandi, 2019). t-Test was conducted to determine the significant difference between the means of the two groups (Kenton, 2019). We assessed the level of acceptability by using the Likert scale and determined the accuracy of the floor plan. Civil engineers obtained a composite weighted mean of 1.2, while architectsobtained a composite weighted mean of 2.33. Hence, the results of civil engineers and architects are considered as least acceptable and moderately acceptable, respectively. In terms of the uniqueness of the design, civil engineers obtained a composite weighted mean of 1.4, while architects obtained a composite weighted mean of 2.33. Hence, the results of civil engineers and architects are least acceptable and moderately acceptable, respectively. In terms of appropriate construction materials, civil engineers obtained a composite weighted mean of 1.4, while architects obtained a composite weighted mean of 2.13. The results of civil engineers and architects were considered as least acceptable and moderately acceptable, respectively. In terms of availability in the market, civil engineers obtained a composite weighted mean of 1.55, while architects obtained a composite weighted mean of 2.25. The results of both groups were moderately acceptable. In terms of the inappropriateness of the materials used, we recommended the use of strong bamboo for a good project. For project demonstration, the miniature version should have colors for attraction. This study was acceptable based on the assessment of the two groups of respondents. On the basis of the conclusions drawn, researchers tended to apply the respondents` recommendations to make the product presentable and be helpful for future researchers. Bamboo houses minimized the use of traditional house sources with useful structures having a high strength-to-weight ratio.
Keywords: circular bamboo house, miniature